Advancing library education : technological innovation and instructional design - Sigal, Ari, 1955- (Hershey, PA : Information Science Reference, 2013)
"This book aims to provide relevant theoretical frameworks, empirical research, and new understandings for those interested in Library and Information Science and the impact new techniques and technologies are having in this area"--Provided by publisher.
Evolving technology, evolving roles for distance education librarians / Lisa Abbott -- Effect of online distance education on library information science programs : the experience at one university / Robert M. Ballard & Yingqi Tang -- I love being able to have my colleagues around the world at my fingertips : connecting teacher-librarians for 21st century work / Jennifer L. Branch & Joanne de Groot -- Equity of experience : shaping pedagogy to provide the best possible learning outcomes for all / Mary Carroll, Sue Reynolds, John Terrell, Bernadette Welch, Paul Mercieca -- Synchronous and asynchronous interaction : access, convenience, and content / Anthony S. Chow -- It takes a village : the value of multiple instructor voices in the online classroom / Nicole A. Cooke -- Digital citizenship and distance education / Lesley S.J. Farmer -- What's in it for me? : professional development in virtual worlds / Esther Grassian & Rhonda Trueman -- Assessment of student learning outcomes in distance education / Vicki L. Gregory -- Online teaching : recent perceptions of faculty at a doctoral research university / Charles B. Hodges, Raleigh Way & Sonya S. Shepherd -- Perceptions and experiences of e-learning among on-campus students / Michelle M. Kazmer, Amelia N. Gibson & Kathleen Shannon -- Faculty experience of online teaching / Julia Khanova -- Traditional to hybrid : social media's role in reshaping instruction in higher education / Rowena Li -- Technology competencies : preparing incoming students in the online education environment / Lili Luo -- Pedagogical evolution in the teaching of reference services enabled by the use of 3D immersive virtual world technology / Nita J. Matzen, Kim Becnel & Geraldine Purpur -- The masters in library & information studies via distance at the University of Wisconsin-Madison / Debra Shapiro -- Bringing the librarian to online courses : cognitive, social, & teaching presence / Nancy Weissman & Karen Swan -- Use of Internet communication technology among distance learners : an investigation among the social science students in Annamalai University / S. Thanuskodi -- Blended learning in digital library learning programme / Sirje Virkus.
"Premier reference source"--Cover.
Includes bibliographical references and index.
Keywords: Library education -- Technological innovations; Distance education; Library science -- Web-based instruction